The one that does, leads: action relations influence the perceived temporal order of graspable objects. - Roberts, K; Humphreys, G (2010)
Perception and action are influenced by the "possibilities for action" in the environment. Neuropsychological studies (e.g., Riddoch, Humphreys, Edwards, Baker, and Willson, 2003) have demonstrated that objects that are perceived to be interacting (e.g., a corkscrew going toward the top of a wine bottle) are perceptually integrated into a functional unit, facilitating report of both objects. In addition, patients with parietal damage tend to report the "active" item of the pair (the corkscrew in the above example) when the objects are positioned for action, overriding their spatial bias toward the ipsilesional side. Using a temporal order judgment task we show for the first time that normal viewers judge that active objects appear earlier when they are positioned correctly for action. This effect is not dependent on a learned relationship between objects, or on the active object being integrated at a perceptual level with the object it is paired with. The data suggest that actions afforded by a correctly positioned active object permeate normal perceptual judgments.